Lateral PbS Photovoltaic Devices for High Performance Infrared and Terahertz Photodetectors - Emmanuel K. Ampadu; Jungdong Kim; Eunsoon Oh (Nanomaterials, 2021)
We fabricated a lateral photovoltaic device for use as infrared to terahertz (THz) detectors by chemically depositing PbS films on titanium substrates. We discussed the material properties of PbS films grown on glass with varying deposition conditions. PbS was deposited on Ti substrates and by taking advantage of the Ti/PbS Schottky junction, we discussed the photocurrent transients as well as the room temperature spectrum response measured by Fourier transform infrared (FTIR) spectrometer. Our photovoltaic PbS device operates at room temperature for wavelength ranges up to 50 µm, which is in the terahertz region, making the device highly applicable in many fields.